Impact of multiple anthropogenic stressors on freshwater: how do glyphosate and the invasive mussel Limnoperna fortunei affect microbial communities and water quality? - Pizarro, Haydee Norma (2015)
The study of the joint effect of multiple anthropogenic stressors is important because the emerging consequences are often unpredictable on the basis of knowledge of single effects. We explored the joint impact of glyphosate and the invasive golden mussel Limnoperna fortunei on freshwater phytoplankton, bacterioplankton andperiphyton, and on the physical and chemical properties of the water. We manipulatedboth stressors simultaneously in a 25-day experiment using outdoor mesocosms; weassayed technical-grade glyphosate acid at four concentrations: 0, 1, 3 and 6 mg glyL-1 under scenarios with and without mussels. The addition of the glyphosatesignificantly increased total phosphorus according to the concentration used; the high clearance rate of L. fortunei significantly decreased phytoplanktonic abundance leading to low values of turbidity. The mussel significantly stimulated the development of filamentous green algae (metaphyton). Interestingly, the combined effect revealed that L. fortunei accelerated the dissipation of glyphosate, which showed a 4-fold decrease in its half-life; this promoted the rapid bioavailability of glyphosate-derived phosphorus in the water. The interaction had a synergistic effect on soluble reactive phosphorus concentrations and was directly dependent on the concentration of glyphosate. A synergistic effect was also observed on bacterioplankton, water turbidity and metaphyton, thus inducing enhanced and rapid eutrophication. The ability of mussels to reduce glyphosate in water may be valued as positive, but our results allow us to predict that the invasion of Limnoperna fortunei in natural freshwater systems contaminated by glyphosate will accelerate the negative impact of the herbicide associated with eutrophication.